2009
DOI: 10.1021/jf901809p
|View full text |Cite
|
Sign up to set email alerts
|

Functional New Acylated Sophoroses and Deglucosylated Anthocyanins in a Fermented Red Vinegar

Abstract: The new acylated polyphenols were isolated from a red-colored vinegar produced via fermentation with purple-fleshed sweet potato storage roots, and identified mainly by MS and NMR. The three acylated sophoroses were determined as 6-O-(E)-caffeoyl-(2-O-(6-O-acyl)-beta-d-glucopyranosyl)-d-glucopyranoses, where acyl was (E)-caffeoyl, p-hydroxybenzoyl, and (E)-feruloyl, respectively. The four acylated anthocyanins were also determined as cyanidin 3-O-(6-O-(E)-caffeoyl-(2-O-(6-O-(E)-feruloyl)-beta-d-glucopyranosyl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 27 publications
(47 reference statements)
2
18
0
Order By: Relevance
“…According to the previous reports of the heteronuclear multiple‐bond correlation (HMBC) and nuclear overhauser effect spectroscopy (NOESY) (Terahara et al ., ), interglycosidic linkage was β‐G 3b ‐(1→2)‐G 3a of a sophorose because G 3b was linked on the G 3a ‐2OH based on the glycosylation shifts of δ G 3a ‐2H 4.36‐4.38 and δ G 3a ‐2C 82.51–82.72 ppm (Table ). Sophorose is always linked to C3 position of aglycon (most are cyanidin and peonidin).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…According to the previous reports of the heteronuclear multiple‐bond correlation (HMBC) and nuclear overhauser effect spectroscopy (NOESY) (Terahara et al ., ), interglycosidic linkage was β‐G 3b ‐(1→2)‐G 3a of a sophorose because G 3b was linked on the G 3a ‐2OH based on the glycosylation shifts of δ G 3a ‐2H 4.36‐4.38 and δ G 3a ‐2C 82.51–82.72 ppm (Table ). Sophorose is always linked to C3 position of aglycon (most are cyanidin and peonidin).…”
Section: Resultsmentioning
confidence: 95%
“…In the recent report, Terahara et al . identified the structure of acylated 5‐deglucosylated anthocyanins through fermentation with purple sweet potato in 2009 (Terahara et al ., ). Montilla et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In their results, purple potato-derived acylated anthocyanins were shown to inhibit a-glucosidase activity [51,52]. This same group also studied the inhibitory effects acylated anthocyanins on the elevation of blood glucose levels in rats [53], and found that the molecular structure responsible for a-glucosidase inhibition was not anthocyanidin itself, but caffeoylsophorose, which is a component of the acylated anthocyanin molecule [54][55][56]. Caffeoylsophorose can be absorbed in vivo in an intact form and subsequently produces caffeic acid and its conjugate [57].…”
Section: Diabetesmentioning
confidence: 99%
“…A famous anecdote about the effect of anthocyanins on vision in Japan describes Royal Air Force pilots during World War II who experienced enhanced vision in the dark α-glucosidase in the small intestinal endothelium, which in turn inhibits degradation and absorption of carbohydrates, thereby ameliorating hyperglycemia. Glycosides, such as C3G, are generally very weak inhibitors of α-glucosidase (Iwai et al, 2006), except for acylated anthocyanins (Matsui et al, 2001a(Matsui et al, , 2001b(Matsui et al, , 2002Terahara et al, 2003Terahara et al, , 2009 and Matsui et al (2004) revealed that caffeoylsophorose (CS), a component of acylated anthocyanins, is the molecular structure responsible for this strong inhibitory activity. Since CS is absorbed in an intact form to produce caffeic acid and its conjugates (Qiu et al, 2011), it is possible that absorbed CS or its metabolites exert an anti-diabetic effect via pathways that do not include α-glucosidase inhibition.…”
Section: Health Benefits Of Anthocyaninsmentioning
confidence: 99%